Chapter Cartoline: la memoria e la sua forma visiva - Pieri, Lara (Public History of Education. Teorie, esperienze, strumenti, 2022)
Cartoline is a didactic method practised by the studies center "Yad Vashem". Starting from the observation and the study of an image, pupils and teachers think about it invlving themselves in a dynamic lesson stimulated by some guided-questions the teacher made. The teachers asked students to create a circle where some images are putted into. Students are asked to choose one of them and to write a words the image suggest them. The image is not contextualized and it shows daily item as a glass of milk or common action as petting an animal. Only afterward the teacher is going to contextualize the image: the glass of milk rapresent the amount of calories (184) assumed by prisoners in concentration camp. A discussion with students is launched.